2017
DOI: 10.1093/jnci/djx148
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Radiotherapy on Complications and Patient-Reported Outcomes After Breast Reconstruction

Abstract: Autologous reconstruction appears to yield superior patient-reported satisfaction and lower risk of complications than implant-based approaches among patients receiving postmastectomy radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
168
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(191 citation statements)
references
References 37 publications
8
168
0
15
Order By: Relevance
“…Autologous reconstruction was also related to higher levels of psychosocial and sexual well‐being, compared with implant‐based procedures . The integration of postreconstruction radiation has also been suggested since the overall quality of life, evaluated from the patient's perspective, does not seem to be compromised . However, the assessment of surgical‐related variables is no longer sufficient to understand the multidimensional construct of quality of life which refers to a combination of physical, psychological, social, and spiritual domains .…”
Section: Introductionmentioning
confidence: 99%
“…Autologous reconstruction was also related to higher levels of psychosocial and sexual well‐being, compared with implant‐based procedures . The integration of postreconstruction radiation has also been suggested since the overall quality of life, evaluated from the patient's perspective, does not seem to be compromised . However, the assessment of surgical‐related variables is no longer sufficient to understand the multidimensional construct of quality of life which refers to a combination of physical, psychological, social, and spiritual domains .…”
Section: Introductionmentioning
confidence: 99%
“…Radiation after implant‐based reconstruction can lead to increased likelihood of forming scar tissue around the implant, resulting in long‐term problems with increased firmness, suboptimal positioning, and the need to remove or replace the implant. There is also an increased risk of complications such as slower healing and infection, which can necessitate implant removal …”
Section: Patient Characteristicsmentioning
confidence: 83%
“…Although instruments designed to collect patient‐reported outcomes following breast reconstruction have been designed, none are specific for women who undergo mastectomy and reconstruction, followed by radiation. Patient‐reported outcomes are worse for women with mastectomy and reconstruction who then receive radiation therapy . However, it is not known how these patients value these outcomes and there is a debate as to whether treatment‐specific measures or general quality of life measures capture the domains most valued by patients.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The retrospective grading of surgical complications in the two moderate‐quality studies reported showed a rate of major complications (CDC grade IIIb) of 9 per cent (6 of 64) at 1 year, and 4·6 per cent (5 of 108) at 2 years. These rates are also likely to reflect under‐reporting compared with the MROC rates of 14·8 per cent (35 of 236) at 1 year and 17·6 per cent (35 of 199) at 2 years. Despite its strengths, the MROC cohort is based on the review of complications from electronic patient records, potentially also underestimating true complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant radiotherapy (PMRT) may have deleterious effects on breast cosmetic outcomes, quality of life (QOL) and surgical complications after immediate BRR. Previous studies evaluating the impact of PMRT on types of immediate BRR showed its potential feasibility in this setting, with lower morbidity rates compared with those of implant‐based procedures. Surprisingly, the rapid adoption of immediate implant‐based reconstruction in about 70 per cent of women, compared with 34 per cent of autologous procedures when PMRT is recommended, may be influenced by surgeon and patient preferences, regardless of current evidence.…”
Section: Introductionmentioning
confidence: 99%